Sarcomatoid chromophobe renal cell carcinoma: Cytohistopathological correlation of a case - Chakrabarti Indranil; Giri Amita; Majumdar Kaushik; De Anuradha (Journal of Cytology, 2010)
Sarcomatoid renal cell carcinomas of the kidney are rare neoplasms constituting about 1-5% of all renal malignant neoplasms. These are aggressive tumors and are commonly associated with conventional (clear cell) renal cell carcinomas, but cases associated with chromophobe renal cell carcinomas are sparse. Cytological features of such lesions have rarely been reported. Here, we report a unique case of a 48-year-old male patient who presented with right flank lump and pain. A fine needle aspiration was performed from the lesion under ultrasound guidance and a cytological diagnosis of pleomorphic sarcoma was made. A right-sided radical nephrectomy was carried out and subsequent histopathology revealed a sarcomatoid renal cell carcinoma with wide areas of necrosis coexisting with chromophobe renal cell carcinoma with calcification. Differentiation of pleomorphic sarcoma from a sarcomatoid renal cell carcinoma is, thus, challenging from cytopathology smears and the differential diagnoses should always be borne in mind while giving a cytopathological opinion.